ANALYSIS OF DIGLOSSIA'S POSITIVE ATTITUDE IN IMPROVING ACADEMIC PERFORMANCE TITLE - Deisy Permata Nurfaizar Sari; Trisa Nurfitri; Ichsan Fauzi Rachman (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research was motivated by the existence of two different types of language which were considered obstacles to students' education and academic achievement. This research aims to reveal the positive attitude of diglossia in improving student academic achievement. The type of research method used is a qualitative approach with literature study data collection techniques. This technique is carried out by searching, reading and analyzing previous written sources. The research subjects are "Bilingualism and Diglossia in Sundanese Language Learning in Bandung City High Schools" in the Journal of the Study of Regional Language, Literature and Culture and Teaching, "Analysis of the Use of Bilingualism and Diglossia in Everyday Speech Acts of Students at SMPN 3 Central Kelumpang, Kotabaru Regency" in Educational Scientific Journal, and "Positive and Negative Perspectives on Diglossia as a Linguistic Phenomenon in Multilingual Societies" at FKIP UNS Journal Systems. The research results based on the analysis obtained show that diglossia has various positive impacts that influence students' education and academic achievement and provides benefits in learning because subjects can be developed in two languages.